Determinants of Auditor’s Ethical Sensitivity: Data from South Kalimantan - Sahla, Widya Ais; Mukhlisah, Nurul; Farida, Lea Emilia (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2019)
This study aims to identify factors that influence the auditor's ethical sensitivity in dealing with work environment situations that will ultimately affect ethical decision making. Specifically this research will examine the influence of ethical reasoning, spiritual well-being, locus of control, age and gender on the auditor's ethical sensitivity. This research is a survey of auditors in South Kalimantan. The analysis technique used is multiple regression. The results showed that spiritual well-being and age did not affect the high and low sensitivity of auditors. While ethical reasoning, locus of control and gender are proven to influence auditor sensitivity.